2023
DOI: 10.3390/nu15030550
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus amyloliquifaciens-Supplemented Camel Milk Suppresses Neuroinflammation of Autoimmune Encephalomyelitis in a Mouse Model by Regulating Inflammatory Markers

Abstract: Multiple sclerosis (MS), a distinct autoimmune neuroinflammatory disorder, affects millions of people worldwide, including Saudi Arabia. Changes in the gut microbiome are linked to the development of neuroinflammation via mechanisms that are not fully understood. Prebiotics and probiotics in camel milk that has been fermented have a variety of health benefits. In this study, Bacillus amyloliquefaciens-supplemented camel milk (BASY) was used to assess its preventive effect on MS symptoms in a myelin oligodendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Disturbance of the gut-brain axis, a bidirectional relationship between the microbiota in the digestive tract and the brain, has been linked to neuroinflammatory response and neurological disorders [29,30]. Cow milk offers a suitable nutritional medium for many microorganisms, including probiotics, due to its high content of essential molecules including carbohydrates, proteins, lipids, vitamins, and minerals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disturbance of the gut-brain axis, a bidirectional relationship between the microbiota in the digestive tract and the brain, has been linked to neuroinflammatory response and neurological disorders [29,30]. Cow milk offers a suitable nutritional medium for many microorganisms, including probiotics, due to its high content of essential molecules including carbohydrates, proteins, lipids, vitamins, and minerals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Hsp65-producing Lactococcus lactis inhibits experimental autoimmune encephalomyelitis by preventing cell migration into the spinal cord [35]. Furthermore, other probiotic species such as Bacillus amyloliquifaciens-supplemented camel milk suppress the neuroinflammation of autoimmune encephalomyelitis by regulating inflammatory markers [29], as well as by regulating SOX5/miR-218 axis orchestration in mouse models [30]. STAT-3 diminished apoptosis and polarized the OLs in LPS-induced immunogenicity, which resulted in defective regulation of MBP and GFAP in OLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic-fed mice had regulated levels of proinflammatory cytokines and myeloperoxidase [ 68 ]. Interestingly, some genetically engineered probiotic strains were far more effective in eliciting an immune tolerance.…”
Section: Antigen Nonspecific Oral Immune Tolerancementioning
confidence: 99%
“…Examples of this are Pediococcus pentosaceus, Enterococcus faecium , and Enterococcus durans from raw camel milk in Morocco [ 4 ], Bacillus subtilis in Iran [ 5 ], and Lactiplantibacillus plantarum in Tunisia [ 6 ]. A large body of evidence confirmed the significant beneficial impacts of probiotics on humans [ 7 , 8 ], animals [ 9 ], and plants [ 10 ].…”
Section: Introductionmentioning
confidence: 99%